Multi‐layer archimedean spiral antenna fabricated using polymer extrusion 3D printing. Issue 7 (23rd April 2016) - Shemelya, Corey; Zemba, Mike; Liang, Min; Yu, Xiaoju; Espalin, David; Wicker, Ryan; Xin, Hao; MacDonald, Eric
ABSTRACT: This work describes the design, fabrication, and testing of an Archimedean spiral or spiral antenna using polymer extrusion 3D printing of polycarbonate base material. The spiral antenna design was simulated using CST Microwave Studio®, and the resulting 3D printed antenna characterized in terms of return loss, directivity, and polarization. The antenna design was embedded into a 3D printed structure using a unique ultrasonic method while a ground plane was inserted through a thermal embedding process. These fabrication methods provide process flexibility, which allows multiple conductive antenna layers to be additively constructed in a single build sequence. The method described can be used to create unique electromagnetic structures such as waveguides directly in a 3D printed dielectric part. The spiral antenna was tested with three variations of microstrip feed line used to match 50Ω impedance and introduce a 180° phase shift between the two arms of the spiral. These include a Duroid balun attached to feed of the antenna after fabrication, a Duroid balun embedded into the polycarbonate during fabrication, and the same microstrip design fabricated out of copper mesh and embedded into the structure using the polycarbonate as a dielectric substrate. The results of these three approaches will be discussed. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1662–1666, 2016